STRATEGI DALAM MENGATASI PENGANGGURAN AKIBAT COVID-19 DI KELURAHAN SUKAGALIH KOTA BANDUNG - Mohamad Ibnu Dinar; Nurul Sifa; Nurfahmiyati (Center for Economic Studies Universitas Katolik Parahyangan, 2022)
The problem of unemployment in Sukagalih Village is caused by the many economic sectors that have been affected by the emergence of the COVID-19 pandemic. Unemployment that occurs is caused by several factors, such as the many occurrences of layoffs (Termination of Employment), the PPKM policy (Enforcement of Restrictions on Community Activities) or Work From Home (WFH) rules. The purpose of this study is to determine the condition of unemployment due to COVID-19 and strategies to overcome unemployment. This research is categorized as a field research using qualitative descriptive methods and using primary data and secondary data collected using interview guidelines. In determining the strategy of reducing unemployment, this study uses triangulation techniques to test the validity of the data. There are three main reasons revealed by informants from the community that they have not or are not working, namely the COVID-19 pandemic, age constraints, and having a history of illness. The results of this study indicate that there are special strategies in overcoming the unemployment problem due to COVID-19 in Sukagalih Village, including providing job training and increasing job vacancies.